Buffer-stock savings and households' wealth response to income shocks - Winfried Koeniger; Giulio Fella; Serafin Frache (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We structurally estimate a buffer-stock savings model using panel data from the Italian Survey of Household Income and Wealth that contains information not only about income and consumption but also wealth. We exploit the information about wealth and the responses of wealth and consumption to income shocks over different time horizons to infer the degree of insurance against permanent and transitory income shocks. The estimated model implies that Italian households can insure 5-10% of a permanent shock and 90-95% of a transitory shock. The degree of insurance against permanent shocks is at the low end of the range of existing estimates for the U.S.
Keywords: E21; D91; E20; 330